Failure Analysis of Weld Metal Cracking in Weld Joint of API 5L X 75 Pipelines Steel - Kamil ALrubaeiy, Abbas; ., .; ., . (International Journal of Engineering and Technology, 2018)
The development of steel alloy which result thin walled, high strength API 5L X75 grade, a restricting parameter controlling widespread use of X75 is the susceptibility to weld metal tracks. The excellent weld ability of this grade of the pipe steel has enhanced the potential for the use of high strength cellulose consumable like E6010 in root pass welding, but the risk of hydrogen assisted cold cracking (HACC) is also increased because of the high strength weld metal. This investigation outlines , the use of grade (E6010) of commercial cellulose consumable to assess conditions leading to hydrogen assisted cold cracking in the diluted weld metal. The research contained clarification of the link among microstructure; preheat temperature and hardness amounts for the weld consumable and its effect on cracking susceptibility. The cracking morphology studies indicated that there are many ways in which the crack can propagate in the weld metal and HAZ region. The mode of cracking observed was microvoide coalescence.Â Â Â